Dinamika Kepatuhan Pajak Kendaraan Bermotor: Pendekatan Kualitatif Dalam Mengeksplorasi Persepsi Dan Sikap Wajib Pajak (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This research delves into the dynamics of motor vehicle tax compliance through a qualitative approach, exploring taxpayers' perceptions and attitudes. The identified key factors shaping attitudes toward tax obligations include regulatory complexity, clarity of rules, and personal experiences. Elements such as fairness perception, trust in the taxation system, and supervisory effectiveness also play crucial roles in forming compliance attitudes. These factors, integrated with psychological aspects, provide an in-depth understanding of taxpayer compliance behavior. While acknowledging challenges like regulatory complexity and economic inequality, the study highlights opportunities, including the application of information technology, fiscal incentive development, and cross-sector collaboration, as strategies to enhance compliance. In conclusion, a holistic and adaptive tax policy strategy, considering both local and global contexts, can foster a transparent, fair, and supportive tax environment for sustainable development.